Augmentation of Reproductive Performance through Controlled Breeding in Goats - Nimse, Pravin Nimse; Amle, Mukund; Khillare, Kavita; Rangnekar, Mahesh; Mali, Ajit; Sonawane, Gokul (The Indian Journal of Animal Reproduction, 2024)
The present experiment was conducted in goats to determine the efficiency of three different estrous synchronization pro tocols viz double PGF2α, CIDR protocol and natural methods i.e. exposing sexually active adult buck to the female goats.  A total of 30 healthy nonpregnant Osmanabadi goats were identified using trans-rectal ultrasonography and divided  equally into the three groups. The goats of Group-I (n=10) were synchronized by using double prostaglandin protocol  (D-Cloprostenol 75μg) administered by intramuscular route 10 days apart, whereas, goats of Group-II (n=10) were  synchronized by adopting a short progestogen treatment (0.3g progesterone) with the intravaginal insertion of CIDR  kept in-situ for a duration of 9 days. Group-III experimental goats (n=10) were exposed with sexually active adult buck  and observed for natural estrus. The estrous synchronization response in Group I, II and III was observed as 80 %, 70 %  & 100 %, respectively with non-significant (p>0.05) difference in the mean estrus onset interval and mean duration of  estrus between all the groups. Exposing matured buck to the female goats was effective to induce estrus in a synchronized  manner. Conception rates of goats belonging to Group I, Group II and Group III were found to be 87.5 %, 57.14% and 70 %,
Keywords: CIDR; D-cloprostenol; Estrous Synchronization; PGF